Regional Risks and Opportunities of Mining in the Asia-Pacific - Ahmad Harakan (ARISTO, 2026)
The book Mining in the Asia-Pacific: Risks, Challenges and Opportunities, edited by Terry O’Callaghan and Geordan Graetz, offers a compelling and timely contribution to the study of extractive industries in one of the world’s most dynamic and contested regions. Mining in the Asia-Pacific is not merely an economic activity, it is a deep political, ecological, and cultural process that shapes the trajectories of states, communities, and environments. Drawing together a wide range of contributors, the volume presents a nuanced understanding of how the mining sector operates across multiple scales: from local land-use disputes to transnational commodity chains. O’Callaghan and Graetz, both scholars from the University of South Australia, frame mining not just as an industrial operation but as a site of ongoing contestation between competing logics, developmentalism, environmentalism, sovereignty, and capital accumulation. Organized into four thematic parts, Theorizing Risk in the Mining Industry, The Major Resources, The Major Issues, and Mitigating Risk, the volume offers a comprehensive structure that guides readers from conceptual reflections to empirical case studies. This format is effective in gradually unpacking the layered nature of mining-related risks. The first section lays a theoretical foundation by problematizing the notion of risk itself, drawing on interdisciplinary approaches from political economy, geography, and environmental studies. The middle sections delve into specific resources (such as coal, gold, and rare earths) and specific issues (including governance, Indigenous rights, and social activism). The final section turns to strategies for risk mitigation, such as regulatory reform, technological innovation, and community engagement, suggesting pathways toward more sustainable and equitable extractive practices.